Efecte ale crizei economice şi financiare în unele localităţi urbane mici din România - Humă, Cristina; Chiriac, Dumitru (Calitatea Vieții, 2012)
The paper aims to outline the main effects of economic and financial crisis on small towns in Romania, with specific analysis in two urban centers: Zimnicea and Videle in Teleorman county. This is because it was found that small towns face much greater difficulties than other cities in our country, a direct result of the recent years’ difficulties: the restructuring of economic activities, with disruptions in the labor market and the reduction of urban functions, migration of the labor force to other more developed urban centers, reducing household incomes and increased poverty phenomenon, etc. The study has an empirical character and is based on quantitative and qualitative information obtained from several institutions (mayoralties, economic agents, etc.), and on statistical data, etc. Also, in the two localities was applied a total of 33 unstructured interviews, conducted between July and October 2011. The results confirmed the difficulties which have to face small towns in this period, and the response measures adopted in households.